Gene expression profiling of adp-glucose pyrophosphorylase (AGPase) in sink and source organs of some cassava varieties with different starch contents in Vietnam - Hong, Nguyen Thi Minh; Ngoc, Le Thu; Hung, Nguyen Mau; Ngoc, Pham Bich; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
Starch is the most widespread and abundant storage carbohydrate in plants. We depend upon starch for our nutrition, exploit its unique properties in industry, and use it as a feedstock for bio-ethanol production. Starch is stored in the form of osmotically inactive, water-insoluble granules in amyloplasts (storage starch) and chloroplasts (transitory starch). The biosynthesis of starch involves not only the production of the composite glucans but also their arrangement into an organized form within the starch granule. Understanding the specific functions played by individual isoforms of enzymes involved in starch biosynthesis pathways will provide important basis for regulation of starch production in plant. A transcript-level analysis of the genes which encode starch-synthesis enzymes is fundamental for assessment of enzyme function and the regulatory mechanism for starch biosynthesis in source and sink organs. In this work, the expression level of the genes encoding ADP-glucose pyrophosphorylase (AGPase) in two local varieties Do Dia Phuong (Do DF) and Trang Hoa Binh (Trang HB) as well as two imported varieties KM94 (Rayong1 X Rayong 90) and KM140 (KM98-1 x KM36) with different starch contents were evaluated by quantitative real-time PCR method. The result of transcript level analysis made the expression profiles of cassava AGPS and AGPL genes (encoding AGPase small and large subunits) during three development periods, 90, 180 and 270 DAP (day after planting). The transcriptional activities of these genes exhibited tissue-specific expression patterns. In particular, AGPS2 and AGPL1 transcripts were predominant in leaves, whereas expression of AGPS1, AGPL2, and AGPL3 appeared to be mostly confined to storage roots. Despite of having disparities between development stages, expression patterns of both AGPS2 and AGPL1 in leaves did not show significant differences amongst investigated cassava varieties. In contrast, transcriptional activities of AGPS1 and AGPL3 in tubers had patterns directly related to the starch contents of the cultivars. These results indicated that AGPS1 and AGPL3 genes likely play an important role in the starch biosynthesis pathway and have potential for regulation of starch production in cassava.